As competências pessoais e profissionais dos artistas dos boi-bumbás de Parintins - AM - Nakauth, Erik de Souza (Brasil, 2025)
This work aimed to identify the professional and personal competencies possessed by artists recognized as renowned in the Boi-Bumbá industry. The main authors of this work are Fleury, Fleury, Bentes, Azevedo, and Bisquerra. The methodology of this research was based on descriptive research with a qualitative character and field research. Through the pre-selected research body, a semi-structured interview was conducted with four artists identified as renowned within the context of the Boi-Bumbá of Parintins, a major annual folkloric festival held in the city of Parintins – AM, executed by artists. As a result, this study identified which artists are considered renowned based on criteria defined by Brazilian jurisprudence, analyzed the reasons that classify them as renowned, and identified the most and least prevalent personal and professional competencies possessed by each of these interviewed artists. "The personal and professional competencies used for the development of this study were, respectively: “Emotional awareness,” “Emotional autonomy,” “Emotional regulation,” “Social skills,” “Life skills and well-being,” “Communication,” “Proactivity,” “Commitment,” and “Learning.